Abscess Formation Secondary to Bowel Perforation as Initial Presentation of Crohn's Disease: A Case Report - Renaldi, Kaka; Hidayat, Leonardus Wibowo (The Indonesian Society for Digestive Endoscopy, 2025)
Crohn's Disease is a gastrointestinal disorder that is more prevalent in the Asian population. Clinical features, such as diarrhea, abdominal pain, and hematochezia, are common manifestations of Crohn's Disease. A 23-year-old male patient presented with a 2-month history of abdominal pain and a mass-like appearance in the right flank. A colonoscopy was performed, which suggests Crohn's Disease. Abdominal CT scan revealed abscess formation. Clinical improvement was not achieved despite the optimization of 5-ASA treatment and the addition of steroids. Abscess drainage was performed, which later revealed ileo-colon perforation with severe adhesion, which was treated with ileo-colon resection, followed by double barrel ileo-colostomy. The pain was improved after surgery and optimization of 5-ASA, steroids, and azathioprine. Intestinal abscess formation should be considered one of the manifestations of Crohn's Disease, which also needs to be investigated for possibilities of perforation. Adequate surgical and medical management can be used to achieve and maintain remission and prevent another intestinal complication. This case report aims to raise awareness of intestinal abscesses due to bowel perforation in Crohn's disease patients.